Efficient and selective carbon dioxide reduction on low cost protected Cu2O photocathodes using a molecular catalyst. Issue 3 (16th January 2015) - Schreier, Marcel; Gao, Peng; Mayer, Matthew T.; Luo, Jingshan; Moehl, Thomas; Nazeeruddin, Mohammad K.; Tilley, S. David; Grätzel, Michael
Abstract : A TiO2 -protected Cu2 O photocathode was paired with a molecular catalyst to drive the efficient and selective reduction of CO2 to CO. Abstract : Photoelectrochemical reduction of CO2 to CO was driven by a TiO2 -protected Cu2 O photocathode paired with a rhenium bipyridyl catalyst. Efficient and selective CO evolution was shown to be stable over several hours. The use of protic solution additives to overcome severe semiconductor-to-catalyst charge transfer limitations provided evidence of a modified catalytic pathway.